17 Socioeconomic status and its influence on survival after acute ST-segment myocardial infarction treated with primary percutaneous coronary intervention. (June 2018) - Steele, Lloyd; Palmer, James; Lloyd, Amelia; Fotheringham, James; Iqbal, Javaid; Grech, Ever
Abstract : Background: In the era of thrombolytic treatment, lower socioeconomic status (SES) was strongly associated with poorer survival after acute myocardial infarction. However, data for ST-elevation myocardial infarction (STEMI) in the current era of primary percutaneous coronary intervention (PPCI) is much more limited. Within existing studies, case identification has often been reliant on coding, a significant proportions of patients have been treated with thrombolysis, or there wasn't an emphasis on door-to-balloon times of less than 90 min. This was often because in these studies data collection started in the early 2000s. Methods: Data was collected for all patients with acute STEMI undergoing PPCI at The South Yorkshire Cardiothoracic Centre, UK between 2009 and 2014. Cox regression analysis was used to assess differences in survival at 30 days, 1 year, and 3 years, by SES quartile (using an area-level measure) after adjustment for confounding factors. Results: There were 3059 STEMI patients. There were no statistically significant differences in survival between SES quartiles at 30 days (p=0.46), 1 year (p=0.69), and 3 years (p=0.75) (figure 1). Risk factors that were significantly differently distributed among SES quartiles were smoking prevalence (p=0.001), age (p=0.001), previous MI (p=0.025), diabetes (p=0.007) and gender (p=0.041). Q1 (the most deprived quartile) had a higher prevalence of smoking (61.9% vs 33.3%), previous MI (39.6% vs 16.0%), and diabetes (39.7% vs 16.2%) compared to Q4 (the least deprived quartile). Q1 also had a greater female preponderance (29.7% vs 24.0%) and a lower mean (SD) age (59.7±12.8 years vs 64.6±12.0 years). In smokers, those within lower SES groups presented with first STEMI at a significantly younger age than those within higher SES groups (Q1: 55.5 years, Q2: 56.4 years, Q3: 58.3 years, Q4: 57.5 years, p=0.01). In contrast, there was no significant difference in mean age at time of first STEMI by SES in never smokers (Q1: 66.5 years, Q2: 65.6 years, Q3: 65.0 years, Q4: 65.8 years, p=0.72). Conclusions: There were no statistically significant differences in either short- or long-term survival post-STEMI between SES quartiles. However, first STEMI occurred at a significantly earlier age in lower SES groups compared to higher SES groups in current smokers but not never smokers, indicating that smoking plays a significant role in the younger age of presentation with STEMI in lower SES groups.